Assessing the Impacts of Opportunity Cost-Related Regret on Experiential Value and Revisit Intention in a Restaurant Setting - Dursun, Incı; Tümer Kabadayı, Ebru; Aralık, Elif (My University, 2023)
The critical role of experiential value in long-term relationships with consumers in the service industry is well accepted. However, individual evaluations of experiential value are likely impacted by psychological factors unrelated to the service providers. This study investigates the hindering impact of opportunity cost-related regret on consumers’ value assessment and revisit intention in a restaurant setting. The paper also examines the impact of financial constraints in developing regret of expenditures for experiences. A mixed-mode survey was conducted in Turkey, 323 valid responses were obtained, and a path analysis was conducted. The results provided additional empirical evidence regarding the strong relationship between experiential value and restaurant revisit intention. More importantly, opportunity cost-related regret was found to impair experien- tial value significantly, although its direct negative impact on revisit intentions was not confirmed. Furthermore, findings revealed that consumers who feel more financially constrained feel more regret after their expenditure on a meal experience, regardless of their monthly income and meal price. Findings provide insights for service providers to understand consumers’ reactions, espe- cially in financially constrained situations.
Keywords: Revisit intention; restaurant; Experiential value; financial constraints; opportunity cost-related regret